Sustainable Tourism Practices and Strategies in Living Museum Management: A Meta-Synthesis Systematic Review - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Darma, Gede Sri; Maradona, Agus Fredy (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study explores sustainable tourism practices in living museum management, focusing on strategies that enhance visitor engagement while ensuring heritage preservation and contributing to sustainable development. It aims to identify key sustainability practices, their implementation, and outcomes, balancing visitor experience and cultural conservation.Methodology: A meta-synthesis systematic review was conducted on empirical studies related to sustainable tourism in living museums. The analysis incorporated highly reputable, peer-reviewed literature to identify patterns, best practices, strategies, and challenges in sustainability, particularly regarding environmental, cultural, and economic dimensions of living museum management.Finding: This study reveals that living museums effectively engage visitors through immersive experiences while advancing sustainable tourism. Key strategies include collaboration with local communities, cultural asset preservation, and environmentally responsible practices to minimise ecological impacts. Furthermore, a holistic approach integrating environmental, cultural, and economic sustainability strategies enhances their roles as heritage custodians and strengthens local development.Conclusion: Living museums provide immersive cultural experiences while balancing heritage conservation and visitor engagement. Their commitment to sustainability, through cultural preservation, ecological responsibility, and economic viability, ensures long-term resilience and meaningful community participation. By integrating comprehensive strategies, these institutions reinforce their role as protectors of heritage and catalysts for sustainable regional development.